Industry Modernization Based on the Principles of Smart Specialization. Part ІI. Establishing the Tools for Monitoring and System Analysis of the Impact of Key Technologies on Industry Modernization - Salikhova, O. B. (Statistics of Ukraine, 2020)
The access to information about the demand of industries in EU and other regions of the world for key enabling technologies (KETs) is becoming increasingly important in the context of New Industrial Strategy for Europe, placing innovations at the core of the policies focused on economic development and rising prosperity of nations. This pushed EU governments to initiate change in the statistical approaches to the assessment of reliability and validity of the current methodological framework KETs Observatory to the effect of the following: updating and extension of the KETs Observatory database (collection of data, computations of indicators); preparation of country profiles and analytical reports on prospective innovation products based on KETs; dissemination of the results of KETs Observatory. Summing up the effort of European researchers to improve KETs Observatory, it is revealed that the central decisions are as follows: (i) extension of technology indicators beyond the patent data, because patents do not cover the full chain of technology generation; (ii) stronger focus on statistical data than on expert conclusions; (iii) use of input-output tables for the assessment of KETs implementation for a broad spectrum of economic activities; (iv) change in the algorithm of turnover indicators, to make it possible to correlate patent activities, technology commercialization and indicators of production output on the KETs basis; (v) launch of international comparisons of the output and the demand for products made on the KETs basis. The article contains an analytical review of recent studies of European researchers in the following fields: (i) introduction and applications of advanced industrial technologies; (ii) regional and sectoral frameworks to support industry modernization on the basis of advanced industrial technologies; (iii) applications of the models of cross-regional cooperation and potential synergies for industry modernization in EU; (iv) analyses of business environment and government support to the involvement of small and medium enterprises in industry modernization; (v) monitoring of the investment promoting industry modernization, giving evidence of change in the nature of investment in capital goods in the era of digitalization and new КЕТs in future. It is shown that neither the wide-scale introduction of advanced technologies in the Ukrainian industry nor the statistical monitoring of this process could become a priority for the Ukrainian government so far. The need for elaborating an observation program for regular interviews of Ukrainian industrial producers about investment in KETs, including advanced industrial technologies, their implementation, gained effects and main barriers, is justified. It is recommended to take due consideration of the EU experiences in preparing technical feasibility reports and constructing adequate data sets required for determining new priorities of science & technology, innovation and industrial policies in Ukraine, to accelerate endogenization of economic growth with account to the current tendencies of KETs development.